ANALISIS PENGARUH VANE TERHADAP KARAKTERISTIK DOUBLE SLOTTED FLAP PESAWAT N2XX DENGAN METODE SIMULASI COMPUTATIONAL FLUID DYNAMIC - Mirna Sari; Gaguk J atisukamto; Gembong Djoni Putranto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
The stability of an airplane is influenced by aerodynamic characteristics, one of which is the lift coefficient (C). The value C is the ratio between the lift force (L) and the dynamic pressure (q). The value of C is determined based on the design of the airfoil shape and the use of the type of flap. The increase in C from the previous study using the simulation method obtained 20.4% with the addition of a flap. This study aims to simulate folds by adding vane (double slotted flap). The methodology in the study uses a simulation of Computational Fluid Dynamic (CFD). The research results of airfoils with the blade having a maximum C of 35.99% are higher than airfoil designs without vane, or 5.77 and 5.61 respectively. The maximum C value of an airfoil with vane or airfoil without using blade occurs at the angle of attack (α) = 16o. The research conclusion informs that vane influences the characteristics of the N2XX aircraft. Vane can minimize the occurrence of a stall (decrease in the value of C) of airplanes in take-off and landing conditions. Keywords: C, vane, double slotted flap, airfoil